An Analysis of Students' Learning Style, Mathematical Disposition, and Mathematical Anxiety toward Metacognitive Reconstruction in Mathematics Learning Process Abstract - Anggoro, Bambang Sri; Agustina, Safitri; Komala, Ramadhana; Komarudin, Komarudin; Jermsittiparsert, Kittisak; Widyastuti, Widyastuti (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
The purpose of this research is to find out whether there is an influence of learning styles, mathematical disposition, and mathematical anxiety on metacognitive reconstruction in mathematics learning and to know how learning styles, mathematical disposition, andMathematical anxietyaffect metacognitive reconstruction in mathematics learning. This research was conducted using theMixed Method. The data processing in this research uses the Structural Equation Model (SEM) through the application of the Lisrel 8.80 program. Based on the data and research results, it can be concluded that: 1) there is an influence of learning style, mathematical disposition, and mathematical anxietyon metacognitive reconstruction in mathematics learning; 2) students with goodmetacognitive reconstruction prefer visual learning style and have a high mathematical disposition and low level of anxiety. Students with medium metacognitive reconstructions category prefer kinesthetic learning styles andhave a moderate mathematical disposition and moderate levels of anxiety. Students with low metacognitive reconstruction categories prefer audio learning styles and have a low mathematical disposition and a high level of anxiety.